THU0589-HPR An Investigation of Emotional Processing Abilities in Fibromyalgia Syndrome. (10th June 2014) - Di Tella, M.; Tesio, V.; Leombruni, P.; Colonna, F.; Bruzzone, M.; Scarati, M.; Fusaro, E.; Torta, R.; Castelli, L.
Abstract : Background: Fibromyalgia (FM) symptoms are not restricted to pain, but often comprise a heterogeneous series of other conditions, including emotional disorders (especially anxiety and depression) 1 . High levels of alexithymia have also repeatedly been reported 2 suggesting that FM patients exhibit a lack of emotional self-awareness. Finally, functional alterations in brain areas responsible for emotional processing (EP) (amygdala and prefrontal cortex) were recently found 3 . Objectives: The present study aimed at analyzing the three subcomponents of EP abilities in FM patients: (1) regulation of emotions, regulation of own emotions (i.e. alexithymia) and emphatic capacities; (2) recognition of others emotions; (3) representation of others affective mental states. The levels of anxiety and depression, and the general cognitive functioning were also assessed. Methods: 22 FM patients were compared to 22 healthy controls (HC) on regulation of emotions (Toronto Alexithymia Scale – TAS-20 and Empathy Quotient – EQ), recognition of others emotions (Ekman 60 Faces), representation of others affective mental states (Reading the Mind in the Eyes – RME), psychological disorders (Hospital Anxiety and Depression Scale – HADS), and general cognitive functioning (Digit Span Forward-Backward – DS F-B, Rey auditory-verbal learning test, Trial making test A-B, verbal fluency, and Tower of London – ToL). Parametric tests such as the unpaired t-test, the chi-square test and the univariate ANOVA were used. Results: Comparison between demographic variables of FM group and HC showed a significant difference for education (t(42)=-5, 58, p <0.0001). For this reason, the analyses were corrected for educational level, as appropriate. T-test analyses showed a significant difference between the two groups on the TAS-20 total score (t(42)=3, 89, p <0.0001), on the EQ (t(42)=2, 76, p =.009), and on the Ekman 60 Faces (t(34, 45)=-4, 24, p <0.0001), for EP assessment; the univariate ANOVA on DS F (F(1, 41)=8, 02, p =.007) and B (F(1, 41)=5, 64, p =.022), and on ToL (F(1, 41)=5, 29, p =.027) for neuropsychological assessment. Instead, chi-square analyses showed a significant difference between the two groups on the HADS total score (χ 2 (1)=11, 02, p =.001) and on the subscale HADS-D (χ 2 (1)=7, 76, p =0.005). Conclusions: The preliminary results showed that FM patients, compared with HC, had a general impairment of EP abilities, with higher difficulties in identifying and expressing their own feelings (i.e. alexithymia), lower empathic skills and lower capacities in recognizing others emotions. FM patients also exhibited higher levels of psychological disorders, especially depression, and some cognitive difficulties. References: Mease P. (2005). Fibromyalgia syndrome: review of clinical presentation, pathogenesis, outcome measures, and treatment. J. Rheumatol. 75, 6–21. Di Tella M. and Castelli L. (2013). Alexithymia and fibromyalgia: clinical evidence. Front. Psychol. 4, 909. Lee S.J., Song H.J., Decety J., et al. (2013). Do patients with fibromyalgia show abnormal neural responses to observation of pain in others? Neurosci. Res. 75(4), 305–15. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4372